2017
DOI: 10.1515/rela-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of native and non-native speakers of English revisited: Do non-native listeners feel the same?

Abstract: This study reports on research stimulated by Lev-Ari and Keysar (2010) who showed that native listeners find statements delivered by foreign-accented speakers to be less true than those read by native speakers. Our objective was to replicate the study with non-native listeners to see whether this effect is also relevant in international communication contexts. The same set of statements from the original study was recorded by 6 native and 6 non-native speakers of English. 121 non-native listeners rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…Lev‐Ari and Keysar advanced that, because foreign‐accented speech reduces processing fluency, speakers come across as less credible. However, given that these results have not been reproduced (Baus et al., 2019; Frances et al., 2018 [regional accent]; Souza & Markman, 2013; Stocker, 2017) or have only partially been reproduced (Hanzlíková & Skarnitzl, 2017; Podlipský et al., 2016), the impact of foreign‐accented speech on credibility cannot be generalized, and further research should investigate under which conditions this effect occurs. It is surprising that true sentences had a higher score when spoken by the reported candidate than by the native candidate or the foreign candidate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lev‐Ari and Keysar advanced that, because foreign‐accented speech reduces processing fluency, speakers come across as less credible. However, given that these results have not been reproduced (Baus et al., 2019; Frances et al., 2018 [regional accent]; Souza & Markman, 2013; Stocker, 2017) or have only partially been reproduced (Hanzlíková & Skarnitzl, 2017; Podlipský et al., 2016), the impact of foreign‐accented speech on credibility cannot be generalized, and further research should investigate under which conditions this effect occurs. It is surprising that true sentences had a higher score when spoken by the reported candidate than by the native candidate or the foreign candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the theory that accent triggers an automatic social categorization has received vast empirical evidence (Giles & Watson, 2013), the role of processing fluency has not been addressed as often, and results have not always been consistent. For example, Souza and Markman (2013), using the same paradigm as Lev‐Ari and Keysar (2010), failed to find an effect of foreign accent on trust (see also Hanzlíková & Skarnitzl, 2017; Podlipský, Šimáčková, & Petráž, 2016, for a partial effect of accent on trust; but Baus, McAleer, Marcoux, Belin, & Costa, 2019; Frances, Costa, & Baus, 2018; Stocker, 2017, for no differences between regional or foreign‐accented speakers and native speakers). Mai and Hoffmann (2014) suggested that bias may possibly originate from both foreignness and processing fluency.…”
Section: Background Literaturementioning
confidence: 99%
“…One of the most salient features of a spoken message is the accent with which it is conveyed, which influences listeners' evaluations. For instance, messages said in a foreign accent are remembered in less detail and are considered less credible than those produced with a native accent (Evans & Michael, 2014;Hanzlíková & Skarnitzl, 2017;Lev-Ari & Keysar, 2010and Podlipský, Šimáčková, & Petráž, 2016; but see Souza &Markman, 2013 andStocker, 2017). Put simply, we do not remember or believe messages produced by foreign accented speakers-i.e., non-native speakers of a language-to the same extent as those produced by native speakers.…”
Section: Introductionmentioning
confidence: 95%
“…That is, accent serves as a cue that a speaker is a non-native speaker, which activates stereotypes-such as foreign accented speakers are less competent and trustworthy than native speakers-which might lead to difficulties in comprehension (Kavas & Kavas, 2008;Lambert, Hodgson, Gardner, & Fillenbaum, 1960;Munro & Derwing, 1995;Ryan et al, 1982). Furthermore, nonnative speakers also evaluate other non-native speakers more negatively (Hanzlíková & Skarnitzl, 2017;Podlipský et al, 2016), highlighting the importance of nativeness in credibility ratings.…”
Section: Introductionmentioning
confidence: 96%
“…A lower competence in pronunciation can for instance disturb the conversation flow by forcing the interlocutor to use more mental resources in processing the speech, reducing processing fluency (Munro and Derwing 1995;Dragojevic and Giles 2016). It has also been shown that foreign-accented speech has an effect on credibility of L2 learners in the perception of native listeners (Lev-Ari and Keysar 2010), as well as L2 listeners (Hanzlíková and Skarnitzl 2017). Moreover, non-native speakers with a strong foreign accent are more likely to be discriminated, for instance, in job interviews (Hosoda and Stone-Romero 2010) or service evaluations (Tombs and Rao Hill 2014).…”
Section: Introductionmentioning
confidence: 99%